ผลของซีพีพี-เอซีพีเพสต์และฟลูออไรด์เจลต่อความแข็งระดับไมโครของผิวเคลือบฟันมนุษย์หลังจากสัมผัสกับเครื่องดื่มโคลา - อุษณีย์ กัลยาธิ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The present study aimed to compare protective effects of CPP-ACP paste and fluoride gel on microhardness of enamel surface eroded by a cola drink and to compare effect of artificial saliva with CPP-ACP paste or fluoride gel on protective effect of microhardness of enamel surface eroded by a cola drink. The specimens were prepared from 60 extracted human lower incisors, randomly divided into 6 groups; 1) CPP-ACP with deionized water 2) CPP-ACP paste with artificial saliva 3) artificial saliva 4) fluoride gel with deionized water 5) fluoride gel with artificial saliva and 6) deionized water. The microhardness of labial enamel surface of the six groups were measured by a microhardness tester. Baseline and eroded hardness were measured and analyzed by Paired-Sample T-Test , Two Way ANOVA and One Way ANOVA. After being eroded by a cola drink, the enamel hardness significantly decreased in all groups studied. The eroded hardness of CPP-ACP paste with artificial saliva group and fluoride gel with artificial saliva group are significantly higher than eroded hardness of the other groups. In conclusion, CPP-ACP paste and fluoride gel can not prevent the hardness of enamel after eroded by a cola drink, but CPP-ACP paste with artificial saliva and fluoride gel with artificial saliva can lessen the degree of demineralization.